Programa de reestructuración técnica en el proceso de fabricación de cartón corrugado en Empaque Industriales Colombianos S.A. (1995)
According to the complete analysis and diagnosis of the current situation carried out in the company, the restructuring program was carried out, proposing new alternatives for change in order to increase productivity in the company working with its own resources mainly in the areas of production, quality, markets, maintenance and occupational health. With an initial investment of $48,000,000, an appreciable economic benefit is obtained in the internal rate of return of 50.35% and in the net present value of $8,152,749.10, which makes the project viable.